Chemical Analysis and Electrochemical Monitoring of Extremely Low-Concentration Corrosive Impurity MgOHCl in Molten MgCl2–KCl–NaCl - Gong, Qing; Ding, Wenjin; Chai, Yan; Bonk, Alexander; Steinbrecher, Julian; Bauer, Thomas (Frontiers in Energy Research, 2022)
MgCl2-KCl-NaCl is a promising thermal energy storage (TES) material and heat transfer fluid (HTF) with high operating temperatures of >700°C for next-generation concentrating solar power (CSP) plants. One major challenge for future implementation of the molten chloride TES/HTF technology arises from the presence of some corrosive impurities, mainly MgOHCl, a hydrolysis product of hydrated MgCl2. Even extremely low-concentration MgOHCl (tens of ppm O in weight) can cause unneglectable corrosion of commercial Fe-Cr-Ni alloys, which limits their service time as the structural materials in the molten chloride TES/HTF system. Thus, the chemical analysis and monitoring techniques of MgOHCl at the tens of ppm O level are vital for corrosion control. In this work, a chemical analysis technique based on direct titration and a high-precision automatic titrator was developed for an exact measurement of MgOHCl at the tens of ppm O level. It shows a standard deviation below 5 ppm O and an average error below 7 ppm O when the concentration of MgOHCl is 36 ppm O. Moreover, compared to other methods available in some literature, it can exclude the influence of co-existing MgO on the MgOHCl concentration measurement. This chemical analysis technique was used to calibrate the previously developed electrochemical method based on cyclic voltammetry (CV), to achieve reliable in-situ monitoring of MgOHCl in the MgCl2-KCl-NaCl molten salt at a concentration low to tens of ppm O level. The in-situ monitoring technique shows the monitoring limitation of <39 ppm O. These two techniques for MgOHCl measurement developed in this work could be used to develop an in-situ corrosion control system to ensure the long service time of the molten chloride TES/HTF system in next-generation CSP plants.